Review of hybrid analysis technique for malware detection - Yus Kamalrul, Mohamed Yunus; Syahrulanuar, Ngah (IOP Publishing, 2020)
Malware is a problem spread out worldwide. Current techniques to analyze these malware are static analysis technique and dynamic analysis technique. Later, the two analysis technique is combined into a technique called hybrid analysis technique. This paper discusses on the current analysis technique and introduces a new approach towards the hybrid analysis technique by introducing memory analysis technique into it. The expected outcome of producing memory analysis technique in hybrid analysis technique will be discussed in the latter part of this paper.